Keanekaragaman Jenis Mangrove di Kawasan Hutan Lindung Pakonjawai Kabupaten Sumba Timur - Ensi Bangu Kahi; Yohana Makaborang; Anita Tamu Ina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
The purpose of this study was to determine the diversity of mangrove species in the Pakonjawai Protected Forest area, East Sumba Regency. The type of research in this study was an ecological descriptive study with a quantitative approach. The sampling technique used was a purposive sampling technique with sampling locations covering 3 observation stations using the line transect method (transect line plot). The results showed that the composition of the mangrove species found consisted of 5 families, 5 genera and 9 species with a total of 337 individuals consisting of 237 individual tree categories, 68 individual saplings and 32 individual seedlings. The mangrove species found were Rhizophora mucronata, Rhizophora apiculata, Rhizopora stylosa, Sonneratia alba, Sonneratia ovata, Avicennia alba, Bruguiera gymnorrhiza, and Sscyphiphora hydrophyllaceae. The diversity index at the tree growth rate was 1.9518, the sampling level was 2.0496 and the seedling level was 1.9588 which means that the diversity of mangrove species is